Modulation of dopamine release by ethanol is mediated by atypical GABAA receptors on cholinergic interneurons in the nucleus accumbens. (29th October 2021) - Yorgason, Jordan T.; Wadsworth, Hillary A.; Anderson, Elizabeth J.; Williams, Benjamin M.; Brundage, James N.; Hedges, David M.; Stockard, Alyssa L.; Jones, Stephen T.; Arthur, Summer B.; Hansen, David Micah; Schilaty, Nathan D.; Jang, Eun Young; et al.
Abstract: Previous studies indicate that moderate‐to‐high ethanol (EtOH) concentrations enhance dopamine (DA) neurotransmission in the mesolimbic DA system from the ventral tegmental area (VTA) and projecting to the nucleus accumbens core (NAc). However, voltammetry studies demonstrate that moderate‐to‐high EtOH concentrations decrease evoked DA release at NAc terminals. The involvement of γ‐aminobutyric acid (GABA) receptors (GABAA Rs), glycine (GLY) receptors (GLYRs) and cholinergic interneurons (CINs) in mediating EtOH inhibition of evoked NAc DA release were examined. Fast scan cyclic voltammetry, electrophysiology, optogenetics and immunohistochemistry techniques were used to evaluate the effects of acute and chronic EtOH exposure on DA release and CIN activity in C57/BL6, CD‐1, transgenic mice and δ‐subunit knockout (KO) mice (δ−/−). Ethanol decreased DA release in mice with an IC50 of 80 mM ex vivo and 2.0 g/kg in vivo. GABA and GLY decreased evoked DA release at 1–10 mM. Typical GABAA R agonists inhibited DA release at high concentrations. Typical GABAA R antagonists had minimal effects on EtOH inhibition of evoked DA release. However, EtOH inhibition of DA release was blocked by the α4 β3 δ GABAA R antagonist Ro15‐4513, the GLYR antagonist strychnine and by the GABA ρ1 (Rho‐1) antagonist TPMPA (10 μM) and reduced significantly in GABAA R δ−/− mice. Rho‐1 expression was observed in CINs. Ethanol inhibited GABAergic synaptic input to CINs from the VTA and enhanced firing rate, both of which were blocked by TPMPA. Results herein suggest that EtOH inhibition of DA release in the NAc is modulated by GLYRs and atypical GABAA Rs on CINs containing δ‐ and Rho‐subunits. Abstract : Alcohol inhibits accumbens dopamine release at high doses. Atypical GABAA antagonists block alcohol's effects on dopamine release. Cholinergic interneurons express atypical GABAA subunits, and GABA currents in cholinergic interneurons are reduced after ethanol, resulting in increased cholinergic firing, which is also blocked by atypical GABAA antagonists. This work suggests a novel effect of ethanol on GABA transmission in the accumbens that has downstream effects on dopamine release.